Effects of molecular weight of polyethylene glycol with size and ratio of fumed silica on rheological behavior of shear thickening fluid - Yanen, Cenk; Solmaz, Murat Yavuz; Aydog, Ercan; Arslanoglu, Hasan (Elsevier Science Sa, 2024)
The rheological models of shear thickening fluids (STFs), which have recently been used in many fields, are estimated using a statistical method in this study. Although research has been carried out to predict the rheo-logical properties of STFs, the variation of the basic parameters affecting the rheological properties has not been studied much in these estimations. To produce shear thickening fluids, silica nanoparticles have been dispersed in polyethylene glycol (PEG). To make the rheological model estimation correctly, nanoparticle ratios (10 wt%, 15 wt%, 20 wt%, 25 wt%), the particle sizes (9 nm, 12 nm, and 14 nm), and the molecular weight of the liquid mediums are produced by changing three different sample set is used. At high shear rates, mixtures of fumed silica (aerosil) and PEG display shear thickening behavior. In the low shear rates (0-200 s-1), this mixture exhibits shear thinning property, while in the high shear rates (200-1000 s-1), shear thickening behavior. Fumed silica-PEG suspensions show pseudoplastic behavior in the first region and dilatant properties in the second region. Equations from theory are used to model the outcomes of the experimental data. Non-Newtonian models are used, and the best model is chosen based on the rheological behavior of the mixes. Herschel-Bulkley is discovered to be the most suitable non-Newtonian model in the first and second regions.
Keywords: Shear thickening fluid; Dilatant property; Pseudoplastic behavior; Rheological models